Multiple sclerosis in adolescents: CT and MR findings. - Osborn, A G; Harnsberger, H R; Smoker, W R; Boyer, R S (American Journal of Neuroradiology, 1990)
The MR and CT findings in 12 adolescents with multiple sclerosis were compared with reported findings in adults. The adolescent group showed a more striking female predominance, more severe disease characteristics, and more frequent infratentorial involvement. Cortical atrophy and abnormal iron accumulation in the basal ganglia were uncommon in the adolescents. Neither group demonstrated a correlation between symptom severity and either extent or location of disease as delineated by MR imaging. MR was more sensitive than CT in detecting demyelinating plaques.